Effect of multi-ions doping on the properties of carbonated hydroxyapatite bioceramic - Safarzadeh, Marjan; Ramesh, Singh; Tan, Chou Yong; Chandran, Hari; Noor, Ahmad Fauzi Mohd; Krishnasamy, Sivakumar; Alengaram, Ubagaram Johnson; Ramesh, Subramaniam (Elsevier, 2019)
The effect of multi-ions (Mg2+, SiO4 4-, Zn2+, Cu2+) doping on the properties of carbonated hydroxyapatite (CHA) prepared by a wet chemical method has been investigated. Different combinations of ions were doped into the CHA and the as-synthesized compacts were sintered at 900 °C prior to body characterization. It was found that regardless of ions doping, the lattice structure of the CHA was not disrupted. In addition, secondary phases were not detected for all the multi-ions doped samples. The XRD and FTIR results further confirmed the presences of a B-Type CHA in the sintered samples. The XRD analysis revealed that the lattice parameters (c/a ratio) increased with dopant addition and resulted in a smaller crystallite size. The FESEM examination also showed the presences of smaller grain size for the multi-ions doped CHA samples thus indicating that the doping was beneficial in suppressing grain coarsening in carbonated hydroxyapatite.